A case study of reservoir characterization and modeling for tidal-dominated estuary reservoir in Ecuador - Cheng Jiwei; Zhang Kexin; Zhang Chaoqian; Li Yunbo; Feng Taoran; Liu Jian; Xu Xianglin; Ma Zhongzhen (Scientific Reports)
Abstract The Oriente Basin, as part of the retro-arc foreland basin system, develops tidal-dominated estuary, where the LU layer exhibits complex sedimentary characteristics in lateral that brings great uncertainty to reservoir characterization using only wells. As a result, it is essential to investigate the sedimentary characteristics of the tidal-dominated estuary by incorporating seismic data. First, four electrofacies are established to characterize the logging response of various lithology combinations in an estuary setting. The seismic facies are then studied by establishing the relationship between seismic waveforms and logging response. Finally, a reservoir model of the LU layer is built by quantitatively characterizing the spatial distribution of sedimentary facies based on the electrofacies and seismic facies. Bottom-water reservoirs are reinterpreted as a combination of the upper edge-water reservoir and the lower bottom-water reservoir based on the characterization results, which are verified by the new drilling wells.